Study of Etiquettes Behavior and Some Physical and Mechanical Properties of a Polymeric Basic Composite (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
In this research the composites materials were prepared by (hand Layout).The composite material consist of the base material(Unsaturated polyester Resin) and consist from the support material is the (Carbide Tungsten) With different Weight ratios (0 ,0.75 ,1.5 ,2.25, 3%) respectively .We have studied the adhesiveness characteristic of the Wear when we change the forcing load for all the specimens and we deepened three loads (5 ,10 ,15 N) with the stability of speed ,we found out that the Wear rate increases with the increase of forcing load we also examined the (Tensile and Hardness) and we found that the value of the hardness increases with the increase of weight fracturing to get its higher value in the rate of 3% .